Rutin and quercetin transformation during preparation of buckwheat sourdough bread. (May 2016) - Lukšič, Lea; Bonafaccia, Giovanni; Timoracka, Maria; Vollmannova, Alena; Trček, Janja; Nyambe, Tina Koželj; Melini, Valentina; Acquistucci, Rita; Germ, Mateja; Kreft, Ivan
Abstract: Sourdough bread was prepared from flour of the common buckwheat ( Fagopyrum esculentum ) and of Tartary buckwheat ( Fagopyrum tataricum ) to follow the transformation of rutin and quercetin in these sourdoughs. During Tartary buckwheat sourdough fermentation, there was conversion of rutin to quercetin. The Tartary buckwheat flour contained 14.6 mg/g rutin and 1.9 mg/g quercetin as dry matter. The sourdough starter contained 1.5 mg/g rutin and an unexpectedly high 12.5 mg/g quercetin. The sourdough contained 3.2 mg/g rutin and 8.1 mg/g quercetin. In the Tartary buckwheat sourdough bread there was no rutin, whereas there was 5.0 mg/g quercetin. Thus, during the sourdough fermentation, the rutin was completely degraded. However, despite the long fermentation time (sourdough, 10 h; bread dough, 5 h), most of the quercetin remained in the dough and appeared in the baked bread. In contrast to Tartary buckwheat bread, neither rutin nor quercetin was present in common buckwheat bread. Information on the persistence of quercetin in sourdough bread is important for designing breads with high concentrations of flavonoids and good functional value. Highlights: Sourdough breads were made from Tartary and common buckwheat flours. Quercetin concentration was unexpectedly high in Tartary sourdough starter. During sourdough fermentation rutin was converted to quercetin. No rutin or quercetin was present in common buckwheat sourdough bread. Quercetin was present in Tartary buckwheat bread dry matter at 5.0 mg/g.